The quality of an English summative test of a public junior high school, Kupang-NTT - Semiun, Thresia Trivict; Luruk, Fransiska Densiana (Universitas Ahmad Dahlan, 2020)
This study aimed at examining the quality of an English summative test of grade VII in a public school located in Kupang. Particularly, this study examined content validity, reliability, and conducted item analysis including item validity, item difficulty, item discrimination, and distracter effectiveness. This study was descriptive evaluative research with documentation to collect data. The data was analyzed quantitatively except for content validity, which was done qualitatively. Content validity was analyzed by matching the test items with materials stated in the curriculum. The findings revealed that the English summative test had a high content validity. The reliability was estimated by applying the Kuder-Richardson’s formula (K-R20). The result showed that the test was reliable and very good for a classroom test. The item analysis was conducted by using ITEMAN 3.0. and it revealed that the the test was mostly constructed by easy items, most of the items could discriminate the students, most distracters were able to perform well, and the most of items were valid.